Carbon capture via novel Cu(II)‐DDA metal–organic frameworks‐based hybrid membranes. Issue 23 (12th March 2022) - Raza, Hamid; Yasmeen, Farhat; Sarfraz, Muhammad; Salman Habib, Muhammad; Ba‐Shammakh, Mohammad; Munawar, Khurram S.; Ahmad, Nazir
Abstract: An important contributor to global warming is the incessant escalation in carbon dioxide gas (CO2 ) levels in the air, mainly attributed to combustion of fossil fuels. A promising strategy to regulate emission of greenhouse gases into open air is the implementation of carbon capture systems at existing and prospective carbon‐releasing infrastructures. Being a distinguished class of mesoporous materials, metal–organic frameworks (MOFs) have great potential to efficiently alleviate CO2 emissions into the atmosphere. Nanocrystals of a newly developed Cu(II)‐DDA MOF were incorporated into polysulfone (PSF) matrix in varying concentrations to fabricate hybrid membranes to enhance their carbon capture efficiency. The prepared mixed‐matrix membranes (MMMs) demonstrated better filler‐matrix interfacial adhesion, homogenous nanofiller dispersal, semicrystalline domains and thermally resistant structure. Gas adsorption tests conducted on both the Cu(II)‐DDA MOF nanocrystals and hybrid membranes indicated good adsorption capacity for CO2 as compared to N2 . Experiments using cast MMMs revealed that doping the polymer matrix with MOF nanofillers increased the CO2 permeability and the CO2 /N2 selectivity of the cast MMMs. In comparison to the pure PSF membrane, the CO2 permeability and CO2 /N2 permselectivity of the composite membrane doped with 5 wt% Cu(II)‐DDA MOF nanocrystals were nearly doubled. Abstract :